Pacific Walrus Coastal Haulout Occurrences Interpreted from Satellite Imagery ... - Anthony S Fischbach; David C Douglas (U.S. Geological Survey, 2022)
This dataset is derived from images from a variety of Earth observing satellite imagery sources collected at known walrus coastal haulouts in Alaska and Chukotka, Russia. Earth observing imagery sources used in this data release include (but are not limited to) optical imagery collections by: (1) the European Space Agency's Sentinel-2 mission, (2) the Plant Labs Planet Scope constellation, and (3) Maxar satellites, as well as synthetic aperture radar imagery collected by: (1) European Space Agency's Sentinel-1 mission, (2) the DLR (German Aerospace Agency) TerraSAR-X satellite, (3) the Umbra Space satellite constellation, (4) the Canadian Radarsat-2 satellite, (5) the Capella Space satellite constellation and (6) the Finnish Iceye constellation. This data package provides: A) geospatial polygon outlines of walrus herds apparent to trained interpreters in satellite images; B) a table listing the satellite images examined that had clear views of the walrus coastal haulout study sites and the area of all walrus ...